2021
DOI: 10.1021/acs.chemmater.1c01945
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure of Multinary Hybrid Lead Halide Perovskites Investigated by Nuclear Quadrupole Resonance Spectroscopy

Abstract: Hybrid organic−inorganic lead halide perovskites have emerged as popular low-cost, solution-processable semiconductors owing to their outstanding optical and electronic characteristics. The structural characterization of these soft solids has proven challenging due to increased structural dynamics and static disorder. Nuclear quadrupole resonance (NQR) may serve as a powerful tool for probing the local structure of the halide anions in bulk and nanocrystalline forms of these perovskites. Here, we characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
3
11
0
Order By: Relevance
“…The smaller splitting between the 1/2 → 3/2 and 3/2 → 5/2 transitions compared to bulk iodines is related to the very large asymmetry parameter η for terminal iodines. All findings clearly confirm the undeniable sensitivity of the NQR technique in probing the perovskite local structure and shall raise further attempts in this direction, especially whenever less disorder is present.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The smaller splitting between the 1/2 → 3/2 and 3/2 → 5/2 transitions compared to bulk iodines is related to the very large asymmetry parameter η for terminal iodines. All findings clearly confirm the undeniable sensitivity of the NQR technique in probing the perovskite local structure and shall raise further attempts in this direction, especially whenever less disorder is present.…”
Section: Resultssupporting
confidence: 66%
“…The NQR technique was also employed in the past for the structural characterization of halide perovskite materials, especially in relation to the local chemical environment probed by the halide, that, presenting nuclear spin I > 1/2, is subject to quadrupolar interaction with the electric field gradient. However, we did not observe any 127 I signal for the m = 3 compound likely because of extreme line broadening caused by inherent disorder associated with the organic component, which in particular has been observed for mixed-cation halide perovskites. Nevertheless, DFT may provide useful feedback about the expected response of iodine in (FA) 3 (HEA) 2 Pb 3 I 11 , so to extend the overall limited amount of results reported in the literature, and narrow the field for future experimental investigation on this or similar compounds. In Table , we report the values of the computed quadrupolar interaction constant ( C q ), asymmetry parameter (η), and corresponding spin-transition frequencies for the 127 I nuclei in two cases of interest, namely, the γ-phase of CsPbI 3 , taken as reference, and our m = 3 layered halide perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting quadrupolar interactions can be described by the nuclear quadrupole coupling constant ( C Q ) and the asymmetry parameter (η). Recent halogen NMR and nuclear quadrupolar resonance (NQR) studies have demonstrated their utility in probing chemical structure and dynamics in solids. ,, Amidst the quadrupolar halogen nuclei, 35 Cl has a moderate quadrupole moment ( Q m ) and high natural abundance (N.A. ), making it a less challenging halogen nucleus for NMR studies compared to 79/81 Br and 127 I (Table ).…”
mentioning
confidence: 99%
“…This is not the case, however, for the lighter elements such as K and Na. This is mainly because the size of the A-cation plays an important role in perovskite stability, , which can be predicted by the tolerance factor . Using K and Na should be good for materials and devices since these elements are cheap and abundant, have low toxicity, and are highly soluble .…”
Section: Introductionmentioning
confidence: 99%